Razred v popularnih televizijskih žanrih - Jontes, Dejan (Teorija in praksa, 2011)
The paper deals with representations of class in television entertainment programmes and chiefly focuses on the locally produced situation comedy It's nice to be a neighbour. It starts with the assumption that the manner in which class is framed importantly contributes to the way audiences perceive the question of class and social inequality. Television entertainment programmes contribute significantly to the social construction of class and myths and stereotypes about certain classes. The paper also considers on the displacement of class discourse into other markers of difference such as discourses of gender and nationality which play an especially important role in situation comedies.
Keywords: Družbeni razredi; Social classes; Television; Televizija; Televizijske oddaje; Television programs; Slovenia; Slovenija